2019
DOI: 10.2174/1389202920666191017163837
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Differentiation of Human Pluripotent Stem Cells: HOX and GATA Transcription Factors as Master Regulators

Abstract: Numerous human disorders of the blood system would directly or indirectly benefit from therapeutic approaches that reconstitute the hematopoietic system. Hematopoietic stem cells (HSCs), either from matched donors or ex vivo manipulated autologous tissues, are the most used cellular source of cell therapy for a wide range of disorders. Due to the scarcity of matched donors and the difficulty of ex vivo expansion of HSCs, there is a growing interest in harnessing the potential of pluripotent stem cells (PSCs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 155 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…In both undifferentiated and differentiated conditions, SPIC and GATA families are predicted as core regulators (Figures 2, 4). The GATA family of transcription factors (GATA1-6) are essential for normal hematopoiesis and a multitude of other developmental processes (Grass et al, 2003;Li et al, 2012;Alsayegh et al, 2019;Castano et al, 2019). GATA-1 regulates terminal differentiation and the function of erythroid, which activates or represses the erythroid-specific gene, such as β-globin locus-binding protein, and it might regulate the switch of fetal to adult hemoglobin in human (Sankaran et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In both undifferentiated and differentiated conditions, SPIC and GATA families are predicted as core regulators (Figures 2, 4). The GATA family of transcription factors (GATA1-6) are essential for normal hematopoiesis and a multitude of other developmental processes (Grass et al, 2003;Li et al, 2012;Alsayegh et al, 2019;Castano et al, 2019). GATA-1 regulates terminal differentiation and the function of erythroid, which activates or represses the erythroid-specific gene, such as β-globin locus-binding protein, and it might regulate the switch of fetal to adult hemoglobin in human (Sankaran et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ongoing challenges of differentiating hPSCs into HSCs that are capable of long-term engraftment, it is necessary to determine the safety of generated blood cells. Accurate control of epigenetic changes in the process of hematopoietic differentiation plays a crucial role in ensuring the safety of generated cells for clinical use [ 111 ]. It has been reported that hematological malignancies can be triggered by the abnormal control of gene expression in HSCs derived from PSCs [ 112 ].…”
Section: Current Challenges Regarding Hscs and Downstream Cells Generated From Pscsmentioning
confidence: 99%
“…In contrast, RA upregulated the expression of a number of genes associated with murine hemogenic endothelial cells and HSPCs, including RAR, KIT, NOTCH, CDKN1B, GATA2 and RUNX1. In addition, the expression of a number of SMAD family members was upregulated, as were ligands of the HH and Wnt signaling pathways, and homeobox A1 (HOXA1) genes that are known to play a role in hematopoietic development (Alsayegh et al, 2019). These results are consistent with the gene set enrichment analyses, and suggest that there is potential crosstalk among the RA/HOX/SMAD/HH/ Wnt signaling pathways that instructs the hemogenic specification of endothelial cells and concomitant downregulation of endothelial cell identity.…”
Section: Mouse and Human Hemogenic Endothelial Cells Arementioning
confidence: 99%